Antibakteri infusa akar mangrove Sonneratia alba pada Escherichia coli dan Staphylococcus aureus - Tuda , Aletheia Marvla Windi; Mongi, Jeane; Kanter , Jabes W.; Pareta , Douglas; Ginting , Amal; Hariyadi, Hariyadi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Antibacterial is a substance that stops and kills the growth of bacteria. Mangrove Sonneratia alba is an exciting plant to use as a medicine because of its antibacterial properties. Secondary metabolite compounds such as alkaloids, phenols, tannins, saponins, triterpenoids, and flavonoids present in the roots are antimicrobial. This study aims to determine the antibacterial activity of mangrove root infusion of Sonneratia alba in Staphylococcus aureus and Escherichia coli. This laboratory study uses the agar diffusion technique with a well to test antibacterial. Using three concentrations, namely 25%, 50%, and 100%, this study found that the infusion of the roots of the Sonneratia alba mangrove 25%, 50%, and 100% showed antibacterial activity against Escherichia coli and Staphylococcus aureus bacteria. The results of the Kruskal-Wallis test showed that Escherichia coli bacteria showed a P value of 0.010<0.05 and Staphylococcus aureus bacteria with a P value of 0.011<0.05, which showed that there was a significant difference between the two types of bacteria because the significant value was less than 0.05.